Urban regeneration like a complex practice in a very transformed historical urban espace: a difficult experience in the present context of the Historical Center of Valladolid (Ciudades, 2017)
The Historical Center of Valladolid can be understood as a resilient urban structure provided with a stable planning framework on a demanding legal and regulatory support, a consolidated context of slowed and continuous transformation that generates some dysfunction in the urban system. A particular case, Valladolid, equipped with a full instrumental articulated by the plans and current programs, which requires the reconsideration of some inertias and dynamics that hinder genuine improvement and preservation. The “normalized” tools authorizes an planning ‘prop’, which should be enriched with projects or specific actions of intervention, and more proactive measures, effectively aimed to the regeneration.
Keywords: urban regeneration; historical centers; resilience; Valladolid